The effects of dynamics and information structures on the solution of conflicts in the global economic and trading system - D. S. PRIYARSONO (MILANG Journal of Mathematics and Its Applications, 2002)
This article exemplifies the application of mathematical (game theoretic) modeling to describe economic phenomenon, i.e., conflicts within the global trading system. The main proposition of this article is that broadening time horizon and promoting information exchange between the parties in conflicts will result in cooperative solution.